2011
DOI: 10.1088/0004-637x/744/1/66
|View full text |Cite
|
Sign up to set email alerts
|

THE ROLE OF STREAMERS IN THE DEFLECTION OF CORONAL MASS EJECTIONS: COMPARISON BETWEENSTEREOTHREE-DIMENSIONAL RECONSTRUCTIONS AND NUMERICAL SIMULATIONS

Abstract: On 2009 September 21, a filament eruption and the associated coronal mass ejection (CME) were observed by the Solar Terrestrial Relations Observatory (STEREO) spacecraft. The CME originated from the southern hemisphere and showed a deflection of about 15 • toward the heliospheric current sheet (HCS) during the propagation in the COR1 field of view. The CME source region was near the central meridian, but no on-disk CME signatures could be seen from the Earth. The aim of this paper is to provide a physical expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
100
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 45 publications
7
100
2
Order By: Relevance
“…They have shown that magnetic reconnection can reverse the twist direction of a flux rope emerging into preexisting fields under the conservation of the total relative magnetic helicity. The complex reconnection of a flux rope with the adjacent field in complex magnetic topology has been also described by, e.g., Lugaz et al (2011), Zuccarello et al (2012), and Masson, Antiochos, and DeVore (2013). Grechnev et al (2008Grechnev et al ( , 2011aGrechnev et al ( , 2013 have found observational evidence of magnetic reconnection between the internal field belonging to the eruptive filament and the preexisting coronal field.…”
Section: Introductionmentioning
confidence: 75%
“…They have shown that magnetic reconnection can reverse the twist direction of a flux rope emerging into preexisting fields under the conservation of the total relative magnetic helicity. The complex reconnection of a flux rope with the adjacent field in complex magnetic topology has been also described by, e.g., Lugaz et al (2011), Zuccarello et al (2012), and Masson, Antiochos, and DeVore (2013). Grechnev et al (2008Grechnev et al ( , 2011aGrechnev et al ( , 2013 have found observational evidence of magnetic reconnection between the internal field belonging to the eruptive filament and the preexisting coronal field.…”
Section: Introductionmentioning
confidence: 75%
“…This result is consistent with who found a positive correlation with the rate of the deflection and the strength of the magnetic energy density gradient. The intrinsic magnetic polarity of the CME flux rope relative to the background coronal magnetic field determines whether and where the magnetic reconnection can occur and consequently deflects the CME (e.g., see simulation work by Chané et al 2005;Zuccarello et al 2012a;Zhou and Feng 2013). If the CMEs intrinsic field is parallel to the ambient field, the CME deflects equator-ward while when the fields are antiparallel, the CME is likely to deflect poleward (Zhou and Feng 2013).…”
Section: Deflection Dependence On the Background Coronamentioning
confidence: 99%
“…Since the launch of STEREO many other methods have been proposed such as forward modelling (Thernisien et al 2006), analysis of height-time diagrams (Mierla et al 2008), and more recently the ellipsoid model (Schreiner et al 2013). Zuccarello et al (2012) have used the triangulation technique to study the deflection of a CME during its path in the solar corona.…”
Section: Introductionmentioning
confidence: 99%